Analisis Pengaruh ANALISIS PENERAPAN PRESENSI SISTEM INFORMASI KEPEGAWAIAN NASIONAL DAN KOMPENSASI TERHADAP KINERJA PNS MELALUI DISIPLIN KERJA SEBAGAI VARIABEL MEDIASI : (STUDI DI SEKRETARIAT DAERAH KABUPATEN MINAHASA SELATAN) - Goldesty Yolanna Ayal; Agus S. Soegoto; Greis M. Sendow (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
This study aims to analyze the effect of the implementation of the National Civil Service Information System (SIMPEGNAS) and compensation on the performance of Civil Servants (PNS) in the Regional Secretariat of South Minahasa Regency, with work discipline as a mediation variable. The study used a quantitative approach through a survey of 159 civil servants and analyzed using Partial Least Square–Structural Equation Modeling. The results of the study show that the implementation of SIMPEGNAS and compensation has a positive and significant effect on the performance of civil servants. In addition, work discipline has been proven to play a role as a mediating variable that positively and significantly mediates the influence of the implementation of SIMPEGNAS and compensation on the performance of civil servants.